2021
DOI: 10.1136/emermed-2020-211027
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic yield of bacteriological tests and predictors of severe outcome in adult patients with COVID-19 presenting to the emergency department

Abstract: BackgroundGuidelines recommend maximal efforts to obtain blood and sputum cultures in patients with COVID-19, as bacterial coinfection is associated with worse outcomes. The aim of this study was to evaluate the yield of bacteriological tests, including blood and sputum cultures, and the association of multiple biomarkers and the Pneumonia Severity Index (PSI) with clinical and microbiological outcomes in patients with COVID-19 presenting to the emergency department (ED).MethodsThis is a substudy of a large ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Surme et al investigated predictors of ICU admission and mortality and also found that high PCT were associated with an increase of the composite outcome of ICU admission and mortality [ 19 ]. Kaal et al also showed similar results in a cohort of 142 patients, and showed that patients with PCT levels above 0.1 ng/mL have an elevated risk of a severe infection [ 20 ].…”
Section: Discussionmentioning
confidence: 71%
“…Surme et al investigated predictors of ICU admission and mortality and also found that high PCT were associated with an increase of the composite outcome of ICU admission and mortality [ 19 ]. Kaal et al also showed similar results in a cohort of 142 patients, and showed that patients with PCT levels above 0.1 ng/mL have an elevated risk of a severe infection [ 20 ].…”
Section: Discussionmentioning
confidence: 71%
“… 4 , 5 , 6 , 7 There was a nearly threefold increased risk of severe COVID‐19 with a lymphocyte count <1.5 x 10 9 /L. 7 However, certain studies failed to determine any significant correlations between absolute lymphocyte count and severe disease, such as the study by Kaal et al 26 We found lower lymphocyte counts in patients who experienced disease progression and death; however, the results were without statistical significance. The result is evidently a consequence of commonly present lymphopenia in most of our patients at admission (median 0.980 x 10 9 /L).…”
Section: Discussionmentioning
confidence: 65%
“…Carbonell et al concluded that elevated procalcitonin level at admission was associated with higher mortality, independent of the possible bacterial co-infection [18]. Surme et al found that high procalcitonin levels were associated with worse outcomes and higher mortality in ICU patients [19]. Tong-Minh et al showed a higher rate of ICU admission and mortality in patients with higher procalcitonin levels in the emergency department [20].…”
Section: Discussionmentioning
confidence: 99%